Wooden Breast Problem in Broiler Chickens - Ahmet Tekeli; Akif Özcan; Hasan Rüştü Kutlu (Turkish Journal of Agriculture: Food Science and Technology)
The present study is designed to attract attention to macroscobic and microscobic findings, causes and economic losses of wooden breast which is a significant muscle problem leading to visual and sensory differences in poultry breast meat quality. Wooden Breast is a crucial problem in poultry industry. It has started to seriously affect poultry production in European and other countries, and especially in United States of America. Woody breast formation is a situation characterized with completely hardened breast fillet or with swelling easily understood when touched. Surface of the fillet contains exudate with petechial bleeding or non-bleeding viscous gelatine. Woody structure called “wooden” can occur not only in breast meat but also in legs. Growth rate, gender, energy level of the feed, amino acid level, and selenium supplement are the factors affecting wooden breast-woody breast meat formation. Shaded colour, surface leak and abnormally hard tissue are seen in macroscopic image of woody breast. In microscopic findings, muscle fibers are less and round. Lesions don’t contain pathogenic micro-organisms, they are aseptic. Colour of the meat of woody breast is brighter and whiter, and (L* value) This muscle problem affects muscles visually and sensorial; but it doesn’t have a negative effect on human health. The more white lines and woody structure in breast meat, the less they are accepted among European consumers.